Single-handed supramolecular double helix of homochiral bis(N-amidothiourea) supported by double crossed C−I···S halogen bonds - Xiaosheng Yan (Nature Portfolio, 2019)
Building an artificial double helix is a compelling challenge, and most strategies rely on the intertwining of two helical strands. Here, in a very different approach, the authors construct a supramolecular double helix from multiple synthetic small molecules chained together by double crossed halogen bonds.